2013
DOI: 10.1177/0748233713484659
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of green tea on antioxidative biomarkers in chemical laboratory workers

Abstract: Chemical materials are environmental contaminants, are extensively used in laboratories, and may cause various forms of health hazards in laboratory workers. Therefore, this toxicity most likely is a result of the oxidative metabolism of chemical to reactive products. As green tea (GT) possesses antioxidant effects, the objective of this study was to examine any amelioration oxidative stress in chemical laboratory workers drinking one cup (3 g/300 ml water) of freshly prepared tea once daily. Baseline characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Caffeinated or alcoholic antioxidant beverages increased salivary TAC in 50% and urinary TAC in 40% of the interventions. In particular, green tea (GT) consumption for 4 or 12 weeks increased salivary TAC in laboratory workers and elderly subjects [ 94 , 120 ], whereas it did not affect salivary TAC of Taekwondo (TKD) athletes after training [ 80 ]. Besides, Benzie et al [ 141 ] found a significant correlation between urinary FRAP values and urinary total phenolic concentrations after GT consumption.…”
Section: Nutritional and Supplement Interventionsmentioning
confidence: 99%
“…Caffeinated or alcoholic antioxidant beverages increased salivary TAC in 50% and urinary TAC in 40% of the interventions. In particular, green tea (GT) consumption for 4 or 12 weeks increased salivary TAC in laboratory workers and elderly subjects [ 94 , 120 ], whereas it did not affect salivary TAC of Taekwondo (TKD) athletes after training [ 80 ]. Besides, Benzie et al [ 141 ] found a significant correlation between urinary FRAP values and urinary total phenolic concentrations after GT consumption.…”
Section: Nutritional and Supplement Interventionsmentioning
confidence: 99%
“…Green tea is particularly well-known for its multiple beneficial effects. Several epidemiological studies have revealed a negative correlation between green tea consumption and the risk of cancer development. Green tea catechins are the major bioactive components of green tea that have been reported to exert protective effects against various types of cancer. However, according to previous reports, intact green tea catechins could not easily be absorbed by the intestines.…”
Section: Introductionmentioning
confidence: 99%
“…In the similar works, previous studies have shown that chemical laboratory, aluminum industry and pesticides workers personnel had been induced oxidative stress [15]- [17].…”
Section: Discussionmentioning
confidence: 56%